(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: In order to develop a proposed model for job redesign at Zagazig University Hospitals, the purpose of this study is to examine the relationships between the organizational influences, the individual-level factors, the main five job characteristics, and person-environment fit. The data was collected from 282 healthcare providers working at Zagazig University Hospitals in Egypt and analyzed by using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results of the study indicated that the main five job characteristics mediate the relationship between individual and organizational factors and person-environment fit. Accordingly, the University Hospital’s management should create supportive organizational environment and provide the medical staff with the necessary competences to be align with redesigned jobs. These redesigned jobs are characterized by involving a wide variety of tasks, feeling of meaningfulness and appreciation from others, performing a clear and a complete job from start to finish, allowing to independently use the appropriate method to perform the job, and having the information about the level of job performance on an ongoing basis. Then, the outcome of these redesigned jobs is enhancing person-environment fit.